The impact of the U.S.-China trade war on Indonesia's financial stability: analysis and implications - Setiyo Purwanto; Nur Endah Retno Wuryandari; Abdy Kurniawan (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2026)
The U.S.–China trade war has generated significant global economic spillovers, yet empirical evidence on its impact on financial stability in third-party emerging economies remains limited. This study examines the effects of tariff escalation, bilateral trade volume, foreign direct investment (FDI), and exchange rate volatility on Indonesia’s financial stability during 2018–2025. Using an explanatory quantitative design, the study employs annual secondary time-series data from official national and international sources and applies multiple regression analysis to test the proposed relationships. The results show that tariff escalation has a statistically significant negative effect on Indonesia’s financial stability, mainly through reduced trade volume and weaker investment flows. Conversely, trade volume and FDI have significant positive effects, indicating their role in strengthening economic resilience. Exchange rate volatility is statistically significant but does not consistently destabilize the financial system, suggesting effective policy responses. These findings provide empirical evidence on how global trade conflicts are transmitted to emerging economies and offer policy insights for enhancing financial resilience amid persistent global uncertainty.